Does the Use of Navigation in Total Knee Arthroplasty Affect Outcomes? - Clayton, Adrian W.; Cherian, Jeffrey J.; Banerjee, Samik; Kapadia, Bhaveen H.; Jauregui, Julio J.; Harwin, Steven F.; Mont, Michael A. (The Journal of Knee Surgery, 2014)
Numerous studies have demonstrated that deviation from the mechanical axis of more than 3 degrees can lead to increased complications and decreased patient satisfaction. The stimulus for navigation of total knee arthroplasty (TKA) was born out of the need for more precise and reliable component alignment. Proponents believe that navigated TKA has the theoretical benefits of improved implant survivorship, better functional outcomes, and greater patient satisfaction. Several studies have shown that intraoperative use of navigation results in superior component positioning when compared with conventional TKA. However, because of concerns about higher institutional costs, intraoperative difficulties, steep learning curves, and potential tracker pin complications, navigation TKA has not gained wide popularity. Moreover, to fully evaluate the use of navigation in TKA, we believe that larger prospective randomized studies are required to clearly define outcomes, as well as economic implications.
Keywords: computer-assisted; total knee arthroplasty; navigation